2011
DOI: 10.1039/c1dt10253b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silicon doped SrMO3 (M = Mn, Co): stabilization of the cubic perovskite and enhancement in conductivity

Abstract: In this paper we report the successful incorporation of silicon into SrMO 3 (M=Co, Mn) leading to a structural change from a hexagonal to a cubic perovskite. For M=Co, the cubic phase was observed for low doping levels (3%), and these doped phases showed very high conductivities ( up to ≈350 Scm -1 at room temperature For M=Mn, the work showed that higher substitution levels were required to form the cubic perovskite (≈15% Si doping), although in these cases the phases were shown to be stable to annealing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 24 publications
(50 reference statements)
6
40
1
Order By: Relevance
“…In particular, we have shown that the partial substitution of these oxyanions at the In/Sc site in Ba 2 (In/Sc) 2 O 5 leads to the introduction of disorder on the oxygen sublattice and a corresponding enhancement in the low temperature ionic conductivity [14][15][16][17][18]. In terms of electronic conducting materials, we have also reported the successful incorporation of silicate, phosphate and sulphate into SrMO 3 (M = Co, Mn), leading to a large enhancement in the electronic conductivity [19,20]. In these latter examples, this large enhancement in the conductivity could be explained by a change from a 2H-perovskite (containing face sharing of octahedra) to a 3C-perovskite (containing corner sharing of octahedra).…”
Section: Introductionmentioning
confidence: 75%
“…In particular, we have shown that the partial substitution of these oxyanions at the In/Sc site in Ba 2 (In/Sc) 2 O 5 leads to the introduction of disorder on the oxygen sublattice and a corresponding enhancement in the low temperature ionic conductivity [14][15][16][17][18]. In terms of electronic conducting materials, we have also reported the successful incorporation of silicate, phosphate and sulphate into SrMO 3 (M = Co, Mn), leading to a large enhancement in the electronic conductivity [19,20]. In these latter examples, this large enhancement in the conductivity could be explained by a change from a 2H-perovskite (containing face sharing of octahedra) to a 3C-perovskite (containing corner sharing of octahedra).…”
Section: Introductionmentioning
confidence: 75%
“…Nb, Sb, Si has been shown to alter the stacking arrangement of the close packed oxygen layers from purely hexagonal to purely cubic (referred to as 2H and 3C respectively). The consequent change from face-shared to corner linked CoO 6 octahedra, leads to a substantial enhancement in the electronic conductivity [28][29][30][31][32]. This stabilisation of the 3C-perovskite framework on Nb, Sb, Si doping can be attributed to a partial reduction of Co 4+ to Co…”
Section: Introductionmentioning
confidence: 96%
“…Indeed, Kozuka et al [37] have shown that the perovskite structure is not stable for such high substitution rates, but Hancock and Slater [41] have shown that the cubic perovskite structure can be stabilized by substituting 3% cobalt by silicon.…”
Section: Methodsmentioning
confidence: 99%